1999
DOI: 10.3354/meps183149
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of nitrogen and sulfur in ectosymbiotic bacteria of marine nematodes (Nematoda, Stilbonematinae)

Abstract: Nematodes of the family Stilbonematinae are known for their hlghly specific association with ectosymbiotic bacteria. These worms are members of the meiofauna in marine, sulfide-rich sediments, where they migrate around the redox boundary layer. In this study, bacterial ectosymbionts of 2 species of marine nematodes, Stilbonema sp. and Laxus oneistus, were shown to be capable of the respiratory reduction of nitrate and nitrite (denitrification). The use of these alternative electron acceptors to oxygen by the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 14 publications
2
46
1
Order By: Relevance
“…The vertical profiles of GAM660-detected rRNA, and GAM660 target cells showed no stratification as might be expected for aerobic chemoautotrophic organisms. However, nitrate respiration has been demonstrated in several endosymbionts, for example, from Solemya reidi (71), Riftia pachyptila (27), and Lucinoma aequizonata (26), as well as in the ectosymbionts of nematodes (25). For the endosymbiotic bacteria, motility of the hosts might be another explanation for the lack of zonation.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical profiles of GAM660-detected rRNA, and GAM660 target cells showed no stratification as might be expected for aerobic chemoautotrophic organisms. However, nitrate respiration has been demonstrated in several endosymbionts, for example, from Solemya reidi (71), Riftia pachyptila (27), and Lucinoma aequizonata (26), as well as in the ectosymbionts of nematodes (25). For the endosymbiotic bacteria, motility of the hosts might be another explanation for the lack of zonation.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the high sulfide concentration in L. oneistus's microenvironment could still select S. majum symbionts, along with other "unwanted" microbes, off the surface of L. oneistus. In fact, symbiotic L. oneistus tolerates much higher concentrations of thiols than does S. majum (8).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, live observations, including the present ones, have never supported this hypothesis. Moreover, experiments have shown that small holes in an otherwise intact coat of bacteria showed no signs of closure over a period of 7 days (Hentschel et al 1999).…”
Section: Ecologymentioning
confidence: 99%
“…They live in sheltered intertidal and subtidal sulfidic sediments, mainly at the interface between the oxidized surface layer and the deeper, anoxic sediment (Ott and Novak 1989;Ott et al 1991). The symbiotic, uniform bacteria which colonize the surface of the worms in various characteristic patterns are chemoautotrophic oxidizers of sulfide and other reduced sulfur compounds (Schiemer et al 1990;Polz et al 1992Polz et al , 1994Hentschel et al 1999). The nematodes appear to graze on their symbionts (Polz et al 1992;Hoschitz et al 2001), and it has been suggested that the bacterial coat is protective against toxic hydrogen sulfide (Ott 1995;Hentschel et al 1999).…”
Section: Introductionmentioning
confidence: 99%